2002
DOI: 10.1182/blood-2002-01-0155
|View full text |Cite
|
Sign up to set email alerts
|

Loss of T-lymphocyte clonal dominance in patients with myelodysplastic syndrome responsive to immunosuppression

Abstract: Evidence suggests that T lymphocytemediated inhibition of hematopoiesis in myelodysplastic syndrome (MDS) contributes to cytopenia in some patients and can be reversed by treatment with immunosuppression. We examined the T-cell repertoires of 12 patients with MDS before and after antithymocyte globulin (ATG)-based treatment by T-cell receptor V␤ (TCR-V␤) spectratype analysis. The average number of TCR-V␤ families with skewed spectratypes, representative of clonal or oligoclonal T-cell populations, was 7.6 in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
5

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 25 publications
3
84
0
5
Order By: Relevance
“…Discussion TCR oligoclonality has been described in PNH 6,7 and has been inferred to reflect an underlying antigen-driven immune response. Such responses have also been reported in AA 7,13 and MDS (Plasilova et al, Blood 2002; 101: 167; abstract #625) 15 -all syndromes of bone marrow failure. TCR clonality is a hallmark of LGL-leukemia, 18,22 which is also characterized by a specific immunophenotype and morphology of expanded clones.…”
Section: Molecular Analysis Of Lgl-like Expansions In Pnh Patientsmentioning
confidence: 59%
See 1 more Smart Citation
“…Discussion TCR oligoclonality has been described in PNH 6,7 and has been inferred to reflect an underlying antigen-driven immune response. Such responses have also been reported in AA 7,13 and MDS (Plasilova et al, Blood 2002; 101: 167; abstract #625) 15 -all syndromes of bone marrow failure. TCR clonality is a hallmark of LGL-leukemia, 18,22 which is also characterized by a specific immunophenotype and morphology of expanded clones.…”
Section: Molecular Analysis Of Lgl-like Expansions In Pnh Patientsmentioning
confidence: 59%
“…Similar findings were also demonstrated in myelodysplastic (MDS) patients (Plasilova et al, Blood 2002; 101: 167; abstract #625). 15 Large granular lymphocytic (LGL) leukemia is a condition characterized by expansion of morphologically typical lymphocytes displaying an effector phenotype; 16 TCR repertoire analysis using flow cytometry and molecular assays is helpful in identifying and characterizing LGL clones and their clonotypes. 17 LGL syndrome is often clinically associated with mono-or multilineage cytopenias, and a single case of PNH with concomitant LGL leukemia has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…We confirmed that CD8 þ /CD57 þ /CD28 -effector T cells are commonly expanded in patients with MDS compared to agematched controls. 4,17 Furthermore, we found that the CD8 þ T cells and T-cell clones from MDS patients express NKG2D and CD244 (2B4), which are activating NK receptors that provide co-stimulation and induce effector functions in T lymphocytes. [46][47][48][49] Unlike traditional mechanisms of antigen co-stimulation with anti-CD28, expression of these molecules on CD8 þ T cells may play an active role in promoting autoimmune disease.…”
Section: Discussionmentioning
confidence: 96%
“…[4][5][6][7][8][9][10][11][12] Univariant and multivariant statistical analyses have identified clinical and biological features associated with clinical response to immunosuppressive therapy, which served as the basis for the generation of response predictive models. [4][5][6][13][14][15][16][17][18] In these analyses, bone marrow hypocellularity, HLA-DR15 phenotype, younger age, lower platelet count and shorter duration of transfusion requirement were associated with response to immunosuppressive therapy. 5,14,19 Analogous to aplastic anemia, elimination of a hematopoietic suppressor T-cell population is hypothesized to underlie treatment response to immunosuppression in this subset of MDS patients.…”
Section: Introductionmentioning
confidence: 99%
“…18 This CD3 deficiency may indicate T-cell activation, since it has also been observed in the blood of individuals with active viral infections 19 and in those T-cells activated nonspecifically in vitro. 20 In the blood of patients with MDS, 21 there is an oligoclonal dominance of T cells with a cytotoxic profile, suggesting specific response to a set of disease-related antigens. The evaluation of lymphocyte function in AML has primarily assessed anti-leukaemia cytotoxic T lymphocytes (CTL) expanded in vitro, with the use of IL-2 or phytohaemagglutinin, from the peripheral blood of patients with AML and CML, who have achieved a chemotherapy-induced remission, 5,22 as well as in those patients with fulminant disease.…”
mentioning
confidence: 99%